2014
DOI: 10.1111/oik.01496
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shift in thermal resistance between generations through maternal heat exposure

Abstract: Given the current rapid climate change, understanding the mechanisms underlying heat tolerance and its plasticity is an important goal of global change biology. Soil fauna communities are especially vulnerable because of their limited dispersal ability. It is generally recognized that transgenerational effects can contribute to the expression of phenotypic plasticity. Nevertheless, transgenerational plasticity in belowground organisms has received relatively little attention in the context of climate change, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 57 publications
4
35
0
Order By: Relevance
“…Without being able to follow single parent crosses it is not possible to assess the heritability of thermal acclimation from the current study. Transgenerational plasticity is, however, increasingly being recognized as a mechanism providing mitigation for some of the negative impacts of climate change (Donelson and Munday, 2015;Zizzari and Ellers, 2014) including increasing CT max across generations (Ho and Burggren, 2012). Highlights  Adult acclimation of CT max was low; 0 to 0.06°C per 1°C increase in temperature  Transgenerational acclimation was up to 5 times greater than adult acclimation  Transgenerational acclimation may buffer climate change in tropical ectotherms…”
Section: Discussionmentioning
confidence: 99%
“…Without being able to follow single parent crosses it is not possible to assess the heritability of thermal acclimation from the current study. Transgenerational plasticity is, however, increasingly being recognized as a mechanism providing mitigation for some of the negative impacts of climate change (Donelson and Munday, 2015;Zizzari and Ellers, 2014) including increasing CT max across generations (Ho and Burggren, 2012). Highlights  Adult acclimation of CT max was low; 0 to 0.06°C per 1°C increase in temperature  Transgenerational acclimation was up to 5 times greater than adult acclimation  Transgenerational acclimation may buffer climate change in tropical ectotherms…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, parental effects may vary across life‐history stages due to trade‐offs. An earlier study on transgenerational effects found that the effects of the parents were strongest in the adult life stage of the offspring (Zizzari & Ellers, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is now generally accepted that plastic responses to environmental conditions during development or adult life can have important fitness consequences. Moreover, it has become apparent that the effect of exposure to biotic or abiotic conditions can be pervasive; as it can last for several generations, or give rise to transgenerational plasticity where parental environment induces phenotypic changes in the offspring or grand-offspring, see, for example [7]. Our understanding of adaptive processes has increased greatly since plasticity is fully recognized as an important parameter in evolutionary biology [8].…”
mentioning
confidence: 99%